Identification and antitumor activity of a novel inhibitor of the NIMA-related kinase NEK6. Issue 1 (December 2018) - De Donato, Marta; Righino, Benedetta; Filippetti, Flavia; Battaglia, Alessandra; Petrillo, Marco; Pirolli, Davide; Scambia, Giovanni; De Rosa, Maria Cristina; Gallo, Daniela
Abstract The NIMA (never in mitosis, gene A)-related kinase-6 (NEK6), which is implicated in cell cycle control and plays significant roles in tumorigenesis, is an attractive target for the development of novel anti-cancer drugs. Here we describe the discovery of a potent ATP site-directed inhibitor of NEK6 identified by virtual screening, adopting both structure- and ligand-based techniques. Using a homology-built model of NEK6 as well as the pharmacophoric features of known NEK6 inhibitors we identified novel binding scaffolds. Twenty-five compounds from the top ranking hits were subjected toin vitro kinase assays. The best compound, i.e. compound8 ((5Z)-2-hydroxy-4-methyl-6-oxo-5-[(5-phenylfuran-2-yl)methylidene]-5, 6-dihydropyridine-3-carbonitrile), was able to inhibit NEK6 with low micromolar IC50 value, also displaying antiproliferative activity against a panel of human cancer cell lines. Our results suggest that the identified inhibitor can be used as lead candidate for the development of novel anti-cancer agents, thus opening the possibility of new therapeutic strategies.